2008
DOI: 10.2176/nmc.48.126
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Cerebellar Anaplastic Glioma Appearing 12 Years After Prophylactic Cranial Radiotherapy for Acute Lymphocytic Leukemia -Case Report-

Abstract: A radiation-induced cerebellar glioma is extremely rare, and the etiology of such a tumor is unknown. We report a rare case of hemorrhagic cerebellar anaplastic glioma occurring 12 years after prophylactic cranial radiotherapy for acute lymphocytic leukemia. We discuss the etiologies of the radiation-induced hemorrhagic cerebellar glioma as a secondary malignancy after radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Worse, radiotherapy might convert the tumor into an aggressive squamous cell carcinoma 21. However, some authors have reported that no cell anaplasia was observed in patients treated with radiotherapy, and only 7% of patients treated with radiotherapy exhibit cell anaplasia 29,30. Some patients who were treated with surgery but not radiotherapy still exhibited similar anaplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Worse, radiotherapy might convert the tumor into an aggressive squamous cell carcinoma 21. However, some authors have reported that no cell anaplasia was observed in patients treated with radiotherapy, and only 7% of patients treated with radiotherapy exhibit cell anaplasia 29,30. Some patients who were treated with surgery but not radiotherapy still exhibited similar anaplasia.…”
Section: Discussionmentioning
confidence: 99%